Comparison Of Oral Health Status And Behavior between First And Fifth Years Of Al-Mustansiriyah Dental Students - Athraa A Mahmood (College of Dentistry/ University of Baghdad, 2017)
Background:Periodontal diseases and dental caries are the most common oral diseases, but they can be adequately prevented by adopting a specific health behavior and plaque control.The study was carried out to determine and compare oral health status; it included both caries experience, gingival health and oral hygiene behavior betweenfirst and fifth yearsof Al-Mustansiriyahdental students. Materials and methods: Total sample of the study consisted of 50 students at first year (25 males, 25 females)and 60 students at fifth year (30 males, 30 females). Plaque andgingival indices,dental caries indices (DMFS and DMFT) wererecorded to evaluateoral health status for each student. Further questionnaires were given to evaluate different oral hygiene habits. Results: The mean values of plaque and gingival indicesin the first year were higher than fifth year for males and females with highly significant difference at (P ≤0.01);whereas the mean values of plaque index were (1.17, 0.83 for males of first and fifth years respectively and 1.02, 0.47 for femaleof first and fifth years respectively)and the mean values of gingival index were(0.89, 0.51 for males of first and fifth years respectively and 0.78, 0.31 for femalesof first and fifth years respectively). As well as, the mean of (DMFS and DMFT) were showed higher values among females than maleswhere (8.88, 6.48 for males and 10.16, 7.08 for females)in first year, while(11.90, 8.73for males and 13.33, 9.16 for females) infifth year. The percentagesof tooth brushing, mouthwash, dental floss, and tooth picks usingfor fifthyear students were higher than first year students. Conclusion: Differences of oral health statusand behavior rates between first and finalyearsstudents can be attributed to low level of dental education infirst year studentswhoseneed the improvements of oral hygiene education in futurewhich include the importance of proper tooth brushing and using of interdental aids to prevent the periodontal diseases and dental caries.